Risk factors, comorbiditiEs and Atherogenic dysLipidaemia in Indian YOUNG patients with dyslipidaemia attending hospital/clinic: REAL YOUNG (dyslipidaemia) study - Iyengar, S; Narasingan, S; Gandhi, Pramod; Jaipuriar, Navneet; Mahilmaran, Asha; Patil, Sachin; Abhyankar, Mahesh; Revankar, Santosh (Journal of family medicine and primary care, 2020)
Objective: To evaluate the pattern of dyslipidaemia, risk factors, and comorbidities in young Indian adults with dyslipidaemia. Methods: A retrospective, multi-centric real-world study included individuals with dyslipidaemia, aged 18 - 45 years, attending to 623 hospitals/clinics across India. Data were collected retrospectively from medical records to note demographics, risk factors (smoking, alcohol consumption, sedentary lifestyle, family history of dyslipidaemia, diabetes mellitus, and hypertension), and clinical details (height, weight, waist circumference, body mass index (BMI), blood pressure, blood sugar, glycated hemoglobin (HbA1c), triglycerides (TG), total cholesterol (TC), low-density lipoproteins (LDL-C), and high-density lipoprotein (HDL-C)).A descriptive analysis and comparative analysis (Mann-Whitney U test and Chi-square test) were done. Results: Of the total 8135 patients, the majority were men (65.0%). Overall, 87.1% of population had one or multiple comorbidities which included the presence of dyslipidaemia alone (12.9%), dyslipidaemia with diabetes and hypertension (39.1%), dyslipidaemia with diabetes (33.6%), and dyslipidaemia with hypertension (14.4%). Sedentary lifestyle was prevalent observation in >50% of the population. Youngest age (18 - 25) group had higher prevalence of hypertriglyceridemia (63.2%), high LDL-C levels (56.8%), and low HDL-C levels (64.6%), while patients from the age group >25 to ≤35 years had the highest incidence of hypercholesterolemia (66.6%). Atherogenic dyslipidaemia was observed in 41.9%, 25.5%, and 23.2% of patients from age groups of ≥18 to ≤25, >25 to ≤35, and >35 to ≤45 years, respectively. Patients with HbA1c ≥6.5% had significantly higher levels of TG, TC, LDL-C, and lower HDL-C compared to those with HbA1c <6.5%. Conclusion: Hypertriglyceridemia, high LDL-C, low HDL-C, and atherogenic dyslipidaemia were prevalent in the young Indian cohort and sedentary lifestyle, and HbA1c ≥ 6.5% were the predominant risk factors of dyslipidaemia.